Pre-post Changes in Implicit Theories of Second Language Acquisition After a Successful Learning Experience - Brown, Christina M.; Seibert Hanson, Aroline E. (Frontiers in Education, 2019)
Students enrolled in language classes often report believing that natural talent is necessary to acquire a second language in adulthood, and this belief can reduce motivation and learning. The purpose of this research was to test if a positive experience promotes the belief that language learning is an ability that can be developed through persistence and effort (i.e., an incremental implicit theory, or growth mindset). We hypothesized that participants would endorse an incremental implicit theory more after using effective study strategies to successfully learn characters in another language. In this study, participants were taught how to read twenty Japanese characters, and their implicit theories of second language acquisition were measured at three time points: days before the learning experience, and immediately and two weeks after the learning experience. Results showed that this brief episode of success in language learning increased an incremental implicit theory of second language acquisition, and this change persisted two weeks later.